Novel insights into relationships between egg corticosterone and timing of breeding revealed by LC‐MS/MS. (1st June 2015) - Larsen, Tom Rosendahl; Fairhurst, Graham D.; De Baere, Siegrid; Croubels, Siska; Müller, Wendt; De Neve, Liesbeth; Lens, Luc
Abstract : Inter‐ and intra‐clutch variation in egg corticosterone (CORT), the major glucocorticoid in birds, may provide insights into how maternal stress levels vary with the timing of breeding and with laying order. Common analytical methods (e.g. immunoassays), however, suffer from cross‐reaction with other steroids, leading to potential overestimation of CORT concentrations which can obscure true hormone–environment relationships and complicate among‐study comparisons. We here apply a new LC‐MS/MS technique, which has recently been shown to avoid the problem of cross‐reactivity due to its high specificity, to quantify CORT concentrations in yolk and albumen in clutches of lesser black‐backed gulls Larus fuscus . We found that CORT concentration exhibited a previously unreported U‐shaped relationship with time of breeding, which we explain as a potential interplay of two forces exerting extra strain on the early and late breeders. Furthermore, results showed an increase in CORT with laying order indicating the energetic expense of egg production. The levels of CORT assessed in this study were significantly lower than those previously reported in studies using immunoassays for CORT analysis. This supports the fact that incorporating chromatography effectively reduces overestimation of CORT due to cross‐reactivity with other steroid hormones, particularly in egg yolk.